Corneal biomechanics in asymmetrical normal-tension glaucoma - Helmy H (Dove Medical Press, 2016)
Hazem Helmy,1 Mahmoud Leila,2 Ahmed Atef Zaki3 1Department of Glaucoma and Optic Nerve Diseases, 2Retina Department, 3Corneal Diseases Department, Research Institute of Ophthalmology, Cairo, Egypt Purpose: We aimed to assess corneal biomechanics using the ocular response analyzer in patients with normal-tension glaucoma (NTG), and to evaluate the relationship between corneal biomechanics and visual field loss. Methods: This was a prospective observational case series including patients with bilateral asymmetric NTG. For all patients, corneal hysteresis (CH), corneal resistance factor (CRF), CH - CRF difference, and central corneal thickness values were matched against the mean deviation (MD) of the visual field and the cup/disc ratio. For paired-eye comparison in each patient, both eyes were categorized into a better-eyes group and a worse-eyes group according to lower and higher corneal-compensated intraocular pressure readings, respectively. Statistical analysis was carried out with the independent-samples Student’s t-test, and the level of statistical significance was set at 0.05. Correlation was assessed using Pearson’s correlation coefficient. Results: The study included 240 eyes of 120 patients. CH was inversely proportional to the MD in the visual field (P=0.01). CRF in both eyes was inversely proportional to the MD of the visual field (P=0.01). CH - CRF difference was directly proportional to the MD of the visual field (P=0.01). For paired-eye comparison, lower corneal-compensated intraocular pressure was associated with higher CH, higher CRF, smaller cup/disc ratio, and less deterioration of MD of visual field. Conclusion: CH, CRF, and CH - CRF are more powerful predictors of NTG progression than central corneal thickness. Keywords: corneal-compensated intraocular pressure, corneal hysteresis, corneal resistance factor